Sarcopenia and risk of infection in adult heart transplant recipients in Japan. (10th February 2022) - Tsuji, Masaki; Kakuda, Nobutaka; Bujo, Chie; Ishida, Junichi; Amiya, Eisuke; Hatano, Masaru; Shimada, Asako; Imai, Hiroko; Shimada, Shogo; Kinoshita, Osamu; Yamauchi, Haruo; Ono, Minoru; et al.
Abstract: Aims: Heart transplantation (HT) is an effective therapeutic option for end‐stage heart failure. Infection is a major cause of morbidity and mortality after HT. Sarcopenia, defined as the loss of muscle mass and strength, is a common comorbidity in HT candidates with end‐stage heart failure. However, the effects of sarcopenia on the occurrence of post‐HT infections are not well understood. Therefore, we explored the association between the skeletal muscle mass and post‐transplant infections in adult HT recipients. Methods and results: We retrospectively examined the records of 135 patients who underwent HT between August 2007 and November 2019 at our institution. Pre‐transplant computed tomography was used to calculate the skeletal muscle index (SMI) at the level of the third lumbar vertebra. Muscle wasting was defined as the SMI of the lowest sex‐based tertiles. The primary endpoint was infections within 6 months of HT. The study included 109 patients (80 men, mean age: 41.6 ± 12.0 years): 37 patients in the muscle wasting group and 72 patients in the non‐muscle wasting group. The mean SMI values in the muscle wasting and non‐muscle wasting groups were 29.9 ± 4.8 cm 2 /m 2 and 40.7 ± 6.7 cm 2 /m 2, respectively. Prior to HT, 108 (99.1%) patients were on left ventricular assist device support, and during that support, the rate of late right heart failure was significantly higher in the muscle wasting group than non‐muscle wasting group ( P = 0.012). Sixteen infections occurred within 6 months of HT. The most common infection sites included the respiratory tract ( n = 5) and the upper gastrointestinal tract ( n = 5), followed by the urinary tract ( n = 4). Overall, 10 patients experienced infections in the muscle wasting group (27.0%) and 6 in the non‐muscle wasting group (8.3%) ( P = 0.009). Two patients in the muscle wasting group required intensive care unit admission, compared to none in the non‐muscle wasting group. Low skeletal muscle mass was associated with infections in the univariate and multivariate logistic regression models (hazard ratio: 3.68, 95% confidence interval: 1.19–11.3; P = 0.023). However, the duration of all‐cause mortality within 3 years did not differ between the groups ( P = 0.56). Conclusions: Low skeletal muscle mass is a predictor of post‐HT infections within 6 months of HT.